Volleyball as a Social Catalyst: Exploring Community Roles in Enhancing Social Interaction Among Youth in Palu City - Alfaisal, Adi; Dewi, Citra; Marzuki, Muhammad (Medpro, 2023)
This study aims to explore and describe the role of the volleyball sports community in fostering social interaction among its members in Palu City, Central Sulawesi. The focus is on understanding how the community functions as a platform for social engagement and personal development. This qualitative descriptive research involved key informants, including community managers, members, and coaches. Data were collected through interviews, observations, and documentation, with the researcher serving as the primary instrument. Data analysis was conducted using techniques such as data reduction, data display, and data verification. Triangulation of sources and methods was employed to ensure the validity of the findings. The study reveals that the volleyball community serves multiple roles in enhancing social interaction among its members: as a place for coming out, exchanging information, showing existence, and mutual support. These roles contribute significantly to the members' social development, allowing them to connect with others, share knowledge, and establish their presence within the broader community. This research highlights the importance of sports communities as vital spaces for social interaction and personal growth, particularly for youth. Such communities can play a significant role in fostering social cohesion and identity formation. This study provides a unique insight into the social dynamics within a sports community, emphasizing the multifaceted roles that such communities play in supporting the social and personal development of their members.